High-Throughput Sequencing Strategy for Microsatellite Genotyping Using Neotropical Fish as a Model - Pimentel, Juliana S. M.; Carmo, Anderson O.; Rosse, Izinara C.; Martins, Ana P. V.; Ludwig, Sandra; Facchin, Susanne; Pereira, Adriana H.; Brandão-Dias, Pedro F. P.; Abreu, Nazaré L.; Kalapothakis, Evanguedes (Frontiers in Genetics, 2018)
Genetic diversity and population studies are essential for conservation and wildlife management programs. However, monitoring requires the analysis of multiple loci from many samples. These processes can be laborious and expensive. The choice of microsatellites and PCR calibration for genotyping are particularly daunting. Here we optimized a low-cost genotyping method using multiple microsatellite loci for simultaneous genotyping of up to 384 samples using next-generation sequencing (NGS). We designed primers with adapters to the combinatorial barcoding amplicon library and sequenced samples by MiSeq. Next, we adapted a bioinformatics pipeline for genotyping microsatellites based on read-length and sequence content. Using primer pairs for eight microsatellite loci from the fish Prochilodus costatus, we amplified, sequenced, and analysed the DNA of 96, 288 or 384 individuals for allele detection. The most cost-effective methodology was a pseudo-multiplex reaction using a low-throughput kit of 1 M reads (Nano) for 384 DNA samples. We observed an average of 325 reads per individual per locus when genotyping eight loci. Assuming a minimum requirement of 10 reads per loci, two to four times more loci could be tested in each run, depending on the quality of the PCR reaction of each locus. In conclusion, we present a novel method for microsatellite genotyping using Illumina combinatorial barcoding that dispenses exhaustive PCR calibrations, since nonspecific amplicons can be eliminated by bioinformatics analyses. This methodology rapidly provides genotyping data and is therefore a promising development for large-scale conservation-genetics studies.